ncRNA-mediated ITGB1 upregulation correlates with poor prognosis and tumor-immune infiltration in gastric cancer - Tianen Li; Wei Su; Zhiqiang Wang; Xiao Wang; Xiaoguang Ma; Rui Zhao (European Journal of Medical Research)
Abstract Background Gastric cancer (GC) is a highly heterogeneous and complex disease. Recently, integrin β (ITGB) superfamily members have been shown to play crucial roles in the initiation and progression of various human cancers. However, the precise role and molecular mechanisms of ITGB1 in GC are yet to be fully elucidated. Methods This bioinformatics and clinical study systematically analyzed the pan-cancer expression patterns and prognostic significance of ITGBs using data from The Cancer Genome Atlas and Genotype-Tissue Expression portals. Multivariate regression analysis was performed to identify key factors influencing GC prognosis. Candidate noncoding RNAs (ncRNAs) potentially regulating ITGB1 expression were identified via expression profiling, coexpression assessment, and survival correlation studies. Furthermore, the associations of ITGB1 and its related long ncRNA MIR99AHG with tumor-infiltrating immune cells, immune cell markers, and immune checkpoint molecules in GC were explored. Results Compared with adjacent normal tissues, the ITGB1, ITGB2, ITGB4, ITGB5, and ITGB8 mRNA levels were significantly upregulated in GC tissues (p < 0.05). Cox regression and Kaplan–Meier survival analyses indicated that ITGB1 upregulation was associated with poor prognosis (univariable hazards ratio = 1.40, 95% confidence interval 1.008–1.956, p = 0.045) and served as an independent prognostic factor (multivariate hazards ratio = 1.46, 95% confidence interval 1.004–2.140, p = 0.048) in patients with GC. The MIR99AHG/hsa-mir-17-5p axis (r = − 0.56, p < 0.001) was identified as the most promising upstream ncRNA-related pathway regulating ITGB1 expression in GC. In addition, ITGB1 expression in GC and adjacent nontumorous tissues was validated using immunohistochemistry (H-score: 35.4 ± 19.2 vs. 28.4 ± 16.2, respectively; p = 0.035). MIR99AHG expression was similarly assessed through in situ hybridization (H-score: 32.4 ± 15.6 vs. 20.5 ± 11.0, respectively; p < 0.001). There was a positive correlation between ITGB1 expression and infiltrating CD4 + T cells (r = 0.17, p < 0.001), M2 macrophages (r = 0.37, p < 0.001), dendritic cells (r = 0.19, p < 0.001), and immune checkpoints (PD-L1, CTLA-4, and CD28). Particularly, high macrophage infiltration was associated with favorable prognosis in GC (p = 0.004). Conclusions Our findings suggest that ncRNA-mediated ITGB1 expression is associated with poor prognosis and tumor-immune infiltration in GC. However, further validation through extensive mechanistic studies and large-scale clinical trials is warranted.